2017
DOI: 10.1063/1.4977078
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of the binary mixtures of the three organic liquids toluene, methanol, and cyclohexane

Abstract: We report on the measurements of diffusion (D), thermodiffusion (D T ) and Soret (S T ) coefficients in binary pairs of the ternary system toluene-methanol-cyclohexane using different instrumental techniques: microgravity measurements (SODI/DCMIX2) on the International Space Station (ISS), thermogravitational column (TGC) in combination with sliding symmetric tubes (SST), optical beam deflection (OBD), optical digital interferometry (ODI) and Counter Flow Cell (CFC). The binary systems have large regions where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“…3(e), for this cell, after an abrupt negative variation of the phase difference due to the application of the thermal gradient, a positive variation occurs followed by a slower negative variation. These two variations of opposite directions are compatible with Soret coefficients of opposite sign, as expected for the polystyrene-toluene-cyclohexane mixture, since toluene-cyclohexane has a negative Soret coefficient [16] while polystyrene-toluene mixtures typi-cally show positive Soret coefficient [33]. In this case, even with only one wavelength, thanks to the well distinguishable dynamics, one can determine the two eigenvalues of the diffusion matrix of the ternary mixture.…”
Section: Quantitative Results On Separation and Diffusionsupporting
confidence: 69%
See 1 more Smart Citation
“…3(e), for this cell, after an abrupt negative variation of the phase difference due to the application of the thermal gradient, a positive variation occurs followed by a slower negative variation. These two variations of opposite directions are compatible with Soret coefficients of opposite sign, as expected for the polystyrene-toluene-cyclohexane mixture, since toluene-cyclohexane has a negative Soret coefficient [16] while polystyrene-toluene mixtures typi-cally show positive Soret coefficient [33]. In this case, even with only one wavelength, thanks to the well distinguishable dynamics, one can determine the two eigenvalues of the diffusion matrix of the ternary mixture.…”
Section: Quantitative Results On Separation and Diffusionsupporting
confidence: 69%
“…The ternary mixture toluene-methanol-cyclohexane is of fundamental interest as it exhibits a miscibility gap and a large region with negative Soret coefficients. The transport and optical properties of binary subsystems were extensively examined [16]. It is known from statistical physics for binary mixtures and confirmed experimentally for methanol + cyclohexane mixture [17], that the diffusion coefficient D drastically diminishes approaching the binodal and should be zero at spinodal, while the thermodiffusion coefficient D T remains constant.…”
Section: Introductionmentioning
confidence: 95%
“…The first system is an almost ideal mixture, which is composed of tetralin (THN), isobutylbenzene (IBB) and dodecane (nC 12 ) [12,25]. For that system, the transport coefficients of its binary subsystems are also well-known [30][31][32]. The second system, composed of cyclohexane, toluene and methanol, exhibits a miscibility gap [27,28,33].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] The second system, studied during DCMIX2 compaign, is composed of toluene, methanol, and cyclohexane. 13,[17][18][19] The DCMIX3 system is composed of water, ethanol, and triethylene glycol, 20 and the last campaign, DCMIX4, includes three additional mixtures of the system toluene, methanol, and cyclohexane; one mixture containing fullerene and a polymer diluted in a binary solvent. 21 The processing of the ISS data revealed that the final results were sensitive to the applied methodology.…”
Section: Introductionmentioning
confidence: 99%